The representation of Autism Spectrum Disorder: a view from the conceptual metaphor theory - Ventura Olivet, Yoselis (2022)
The purpose of this research was to analyze the representation of the Autism Spectrum Disorder (ASD) by parents of children  diagnosed with this condition, in Chile, about: i) the ASD as disorder, ii) their self-image as parents, iii) their sons with ASD, and iv) teachers and mental-health specialists. The methodologies by Coll-Florit y Climent (2019) and Saban et al. (2007) were used. It was demonstrated that the conceptualization of ASD is closely related to opposition to forces and nature. Regarding the teachers, a resistance to change their educational paradigm is outlined, and the mental-health specialists are conceived as passive agents.